Jakość głosu nauczyciela - wpływ czynników zewnętrznych i wewnętrznych = The quality of teacher`s voice - impact of internal and external factors - Przybylska-Zielińska, Anna (Zielona Góra: Instytut Pedagogiki. Wydział Pedagogiki, Psychologii i Socjologii. Uniwersytet Zielonogórski)
The quality of teacher?s voice - impact of internal and external factors. The author shows internal and external factors which have impact on the quality of teacher?s voice. External factors concern workplace conditions, such as humidity and temperature of the air, pollination, noise. Internal factors refer to psychophysical condition of the teacher, his/her life style, health state, resistance to stress, and education.
Keywords: emisja głosu; czynniki zewnętrzne i wewnętrzne wpływające na jakość głosu; voice emission; external and internal factors; quality of teacher's voice; noise; stress